Sustainable Ecotourism: A Catalyst for Habitat Conservation and Community Development - Debashis Debnath (AG Volumes, 2026)
conservation with economic development. This paper examines two critical human activity systems related to ecosystems: habitat conservation and ecotourism. Habitat conservation encompasses the preservation, protection, and restoration of biodiversity, natural resources, and ecosystems to ensure sustainable development. Ecotourism serves as a conservation tool that provides an economic alternative to more invasive and extractive activities, thereby raising public awareness of environmental issues. The synergy between these two systems forms the foundation of environmental services aimed at sustainable development. This study explores emerging trends in sustainable ecotourism, focusing on its potential to protect habitats while enhancing the livelihoods of local communities. By analyzing case studies from diverse regions, the research underscores the importance of balancing ecological integrity with the needs of local populations, illustrating how ecotourism can function as a tool for habitat conservation and sustainable planning. The paper delves into the symbiotic relationship between ecotourism and habitat conservation. Various studies from different areas, such as Valmiki National Park (wildlife tourism), Nayagarh in Odisha (community-based ecotourism) and Majuli Islands (heritage ecotourism) highlight the potential of sustainable ecotourism to contribute to biodiversity conservation, poverty alleviation, and sustainable development. By understanding the challenges and opportunities associated with this approach, policymakers, practitioners, and communities can collaborate to create a more equitable and environmentally sustainable future.